2017
DOI: 10.1111/chso.12256
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, Emotion and Behaviour: An Intervention Study with Chinese Migrant Children

Abstract: Migrant children in China who move from rural to urban areas face significantly greater emotional and behavioural challenges than their urban peers. In recent decades, western countries have used mindfulness to enhance child psychosocial and behavioural outcomes. This approach has not yet been applied to rural‐to‐urban migrant children in China. This study utilised one‐group pretest‐posttest design to examine the effects of a 4‐week school‐based mindfulness intervention on Chinese migrant children's emotions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…This 14 item version of the SDQ assesses both internalizing and externalizing behaviors. The SDQ Chinese version, which we used, has shown good validity, reliability, and cultural applicability among youth in China (Yeung and Lee, 1999;Marsh et al, 2000;Leung et al, 2016;Lu et al, 2018). This study's Cronbach's alpha for these 14 items was 0.81.…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…This 14 item version of the SDQ assesses both internalizing and externalizing behaviors. The SDQ Chinese version, which we used, has shown good validity, reliability, and cultural applicability among youth in China (Yeung and Lee, 1999;Marsh et al, 2000;Leung et al, 2016;Lu et al, 2018). This study's Cronbach's alpha for these 14 items was 0.81.…”
Section: Methodsmentioning
confidence: 78%
“…Childhood EBPs are also associated with negative mental states such as anxiety, academic under-achievement, delinquency, and depression (Broidy et al, 2003;Bahmani et al, 2016). This link between lowincome students and the proclivity for academic under-achievement and the associated EBPs can be particularly devastating for an adolescent in the Chinese school system (Lu et al, 2018;Chen et al, 2018). In China, those who come from lower socioeconomic status families often find that education is their primary way to improve their lives and obtain a well-paying job in the competitive Chinese labor market (Ye, 2015;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The shortened SDQ contained 14 items regarding youth internalising and externalising problems. We used the Chinese version of SDQ, which has shown good reliability, validity, and cultural applicability among Chinese adolescents (Leung, Marsh, Craven, & Abduljabbar, ; Lu et al, ; Marsh, Kong, & Hau, ; Yeung & Lee, ). The Cronbach's alpha of these 14 items was 0.82 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The positive effects of mindfulness interventions are consistent across cultural contexts, including the Netherlands, Hong Kong, and China (Bögels, Hoogstad, van Dun, de Schutter, & Restifo, ; Lam, ). In a recent study of 69 Chinese rural migrant children, Lu, Rios, and Huang () found that children's level of mindfulness was associated with reduced internalising and externalising behaviours. Specifically, for children whose post‐test mindfulness score increased by more than 6 points, internalising problems and externalising problems decreased by 2.8 points and 3.1 points, respectively.…”
Section: Background Literaturementioning
confidence: 99%
“…Additionally, their patterns of emotions, attitudes, behavior, and cognition are still developing ( Kar et al, 2015 ). Some studies have found that MT is a useful approach for simultaneously decreasing internalizing and externalizing adversity and increasing resilience among both young kids and adolescents ( Bluth & Eisenlohr-Moul, 2017 ; Bogels et al, 2008 ; Lu et al, 2018 ). In addition, researchers discovered that great trait mindfulness is beneficial ( Broderick & Metz, 2009 ; Schonert-Reichl & Lawlor, 2010 ) for navigating hard issues ( Biegel et al, 2009 ), such as how individuals experience and cope with their negative emotions (e.g., anxiety, stress), enhance resilience ( Bluth & Blanton, 2014 ; Tan, 2016 ) and improve mental well-being ( Huppert & Johnson, 2010 ).…”
Section: Introductionmentioning
confidence: 99%